2020
DOI: 10.18203/2320-1770.ijrcog20201815
|View full text |Cite
|
Sign up to set email alerts
|

Sweeping of the fetal membranes and its effect on duration of pregnancy in low risk cases

Abstract: Background: This study aimed to determine effectiveness of sweeping of membranes on the duration of pregnancy at term, and its effect on maternal and neonatal outcomes.Methods: In this prospective study, 145 women with uncomplicated pregnancy at 39 weeks or more gestation who were attending regular ANC clinic, were recruited for study, out of them 60 were cases (sweeping group) and 85 were control (no sweeping group). Primary outcome measure was occurrence of spontaneous labour and total duration of pregnancy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…This finding contrasts with the results of Kathleen Putnam et al [58], who reported an elevated risk of clinical chorioamnionitis in the membrane-stripped group (10.3% vs. 6.0%). Hend and colleagues [61] also noted two pregnancies in the stripped group complicated by intrapartum chorioamnionitis, compared to only one in the control group, though the results were not statistically significant (p>0.05). These discrepancies may be attributed to the multiple membrane sweep procedures conducted in their respective studies.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This finding contrasts with the results of Kathleen Putnam et al [58], who reported an elevated risk of clinical chorioamnionitis in the membrane-stripped group (10.3% vs. 6.0%). Hend and colleagues [61] also noted two pregnancies in the stripped group complicated by intrapartum chorioamnionitis, compared to only one in the control group, though the results were not statistically significant (p>0.05). These discrepancies may be attributed to the multiple membrane sweep procedures conducted in their respective studies.…”
Section: Discussionmentioning
confidence: 95%
“…This is particularly relevant in resource-poor settings in Sub-Saharan Africa where access to maternal and neonatal health services can be prohibitively expensive. This straightforward procedure can be performed by midwives or community health extension workers when properly trained, offering a viable alternative for women who prefer to avoid formal induction of labor [58][59][60][61][62][63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation